The Representation of Media Power in Editorial Languages on Pikiran Rakyat Daily Newspaper - Rahzanie, Risha Devina; Rustono, Rustono (Pascasarjana Universitas Negeri Semarang, 2019)
The title of the Plan becomes a media that describes editorial powers in expressing their opinions. This study aims to analyze the representation of power as reflected in the editorial on terrorism-themed articles in the Pikiran Rakyat General Daily with the article title